Investigations on dose proportionality and drug-drug interaction for a fixed-dose combination of trazodone and gabapentin - Ruggieri, Alessandro; Picollo, Rossella; Vecchio, Alessandra Del; Calisti, Fabrizio; Dragone, Patrizia; Comandini, Alessandro; Rosignoli, Maria T.; Cattaneo, Agnese; Donath, Frank; Wedemeyer, Ralph-Steven; Todorova-Sanjari, Marina; Warnke, André; et al. (International journal of clinical pharmacology and therapeutics, 2021)
To establish dose proportionality for trazodone and gabapentin at fixed ratios of trazodone/gabapentin 2.5/25, 10/100, and 30/300 and investigation of potential drug-drug interaction at a dose of 10/100. 29 out of 30 healthy subjects completed this single-center, open-label, randomized, 5-period cross-over trial with single-dose fasted administrations. Administrations were separated by a washout period of at least 6 days. Blood samples were drawn until 48 hours post dose. A validated liquid chromatography-tandem mass spectrometry method (LC-MS/MS) was applied for determination of trazodone and gabapentin in plasma. The lower limits of quantitation (LLOQ) were 1.00 ng/mL and 5.00 ng/mL for trazodone and gabapentin, respectively. Adverse events (AEs) were analyzed in the study population descriptively. Plasma concentrations were characterized thoroughly. For trazodone, assessment of proportionality (power model/pairwise-comparison by ANOVA) showed proportionality for AUC over all doses and for C between the middle and high dose. For gabapentin, a less than proportional increase in both metrices was present with a likely proportional increase from 25 to 100 mg only. Considering common bioequivalence criteria, absence of pharmacokinetic interaction was confirmed comparing the combination and individual agents. 23 subjects experienced 53 AEs during the trial, the most frequent being fatigue (20 cases/15 subjects) and dizziness (14 cases/11 subjects). No serious AEs were reported. To our knowledge, for the first time, proportionality for trazodone at doses of 2.5 to 30 mg and for gabapentin at doses of 25 to 300 mg was investigated. Absence of a pharmacokinetic interaction was shown.